2016
DOI: 10.1038/sc.2016.168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imidafenacin on the urodynamic parameters of patients with indwelling bladder catheters due to spinal cord injury

Abstract: Study design:A retrospective study.Objectives:To investigate the effect of imidafenacin on the urodynamic parameters of patients with indwelling bladder catheters due to spinal cord injury (SCI).Setting:Spinal center (Tokyo, Japan).Methods:Imidafenacin was prescribed to 34 patients with SCI who had a low cystometric volume and/or detrusor compliance according to a urodynamic study. A low cystometric volume and detrusor compliance were defined as <200 ml and <20 ml cm−1 H2O, respectively. The urodynamic study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Anticholinergic drugs are considered the standard treatment for NDO. The positive effects of oxybutynin, trospium chloride, tolterodine, propiverine, and imidafenacin in increasing the bladder capacity and reducing the intravesical pressure have been documented in several studies . However, antimuscarinic drugs are far from an ideal tool for the management of NDO, especially because their adverse effects, including constipation, significantly limit long‐term treatment in neuropathic patients with primary impaired intestinal motility attributable to an underlying neurological condition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticholinergic drugs are considered the standard treatment for NDO. The positive effects of oxybutynin, trospium chloride, tolterodine, propiverine, and imidafenacin in increasing the bladder capacity and reducing the intravesical pressure have been documented in several studies . However, antimuscarinic drugs are far from an ideal tool for the management of NDO, especially because their adverse effects, including constipation, significantly limit long‐term treatment in neuropathic patients with primary impaired intestinal motility attributable to an underlying neurological condition .…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of oxybutynin, trospium chloride, tolterodine, propiverine, and imidafenacin in increasing the bladder capacity and reducing the intravesical pressure have been documented in several studies. 4 However, antimuscarinic drugs are far from an ideal tool for the management of NDO, especially because their adverse effects, including constipation, significantly limit long-term treatment in neuropathic patients with primary impaired intestinal motility attributable to an underlying neurological condition. 5 Furthermore, a substantial proportion of patients do not respond adequately to anticholinergic treatment in terms of its efficacy, even when a higher dose is used than is usually administered to patients with idiopathic overactive bladder (iOAB).…”
mentioning
confidence: 99%
“…At present, anticholinergic (antimuscarinic) drugs are recommended as the first-line treatment for NLUTD. Although some studies have reported that anticholinergic (antimuscarinic) medications can effectively improve urodynamic parameters in patients with NLUTD ( Madhuvrata et al, 2012 ; Sugiyama et al, 2017 ), these medicines are associated with side effects (e.g., dry mouth and constipation) that limit their use in the long term ( Averbeck and Madersbacher, 2011 ; Manack et al, 2011 ; Wagg et al, 2012 ). Therefore, there is a clear need to develop novel, effective, and safe therapeutic modalities for NLUTD.…”
Section: Introductionmentioning
confidence: 99%
“…3 We would like to emphasize that settings where more than one random covariate should be accounted for, are supposed to be frequently encountered in applied research. For example, in order to assess the efficacy of a treatment in spinal cord injury patients with respect to bladder function 4 , it may be sensible to adjust not only for the baseline measurement of the outcome (e.g., detrusor pressure), but also for another baseline variable, which is presumably correlated with the outcome (e.g., cystometric volume). In a recently published clinical trial from stroke research, the NIHSS score at 24 hours after the intervention was considered as the primary outcome, and group means were adjusted for NIHSS at baseline 5 .…”
Section: Introductionmentioning
confidence: 99%